A post-conference evaluation of the 2015 National Occupational Injury Research Symposium. (February 2017) - Schuler, Christine R.; Castillo, Dawn N.; Menéndez, Cammie Chaumont; Sinelnikov, Sergey; Webb, Sydney; Chavez, Emily
Abstract: Introduction: The National Occupational Injury Research Symposium (NOIRS) is the only national forum focused on occupational injury research findings, data and methods, and prevention strategies; it has been convened every 3–5 years since 1997. Held in May 2015, the 6th symposium's theme was "Advancing Occupational Injury Research through Integration and Partnership." Organizers requested that attendees complete a post-meeting evaluation to assess meeting impact, and gather information useful in planning subsequent meetings and activities. Method: The questionnaire was publicized via a quick response code and link to the survey on symposium book cover, and mentioned at each scientific session. The online survey was designed to be completed in ≤ 15 min; no identifying information was collected. Survey link remained open for seven days post-symposium. Results: About 50% of registered attendees responded. Almost half were attending their first NOIRS. Most were researchers (69%); 45% were affiliated with government and 38% with university or research institute. Five of six reported that the symposium mostly or completely met expectations. Reasons for attending included gaining exposure to new areas of research (87%), sharing their research (80%), and to develop new ideas for conducting research (79%). The majority (90%) reported that the symposium provided adequate networking opportunities. The conference venue was reported as good or better by 69%, moreso among repeat attendees (77%) compared to first-timers (61%). Discussion: The evaluation demonstrated that NOIRS was valuable to attendees, and provided a forum for sharing research results, developing new research ideas, and networking. Respondents provided input on different aspects of NOIRS and suggestions useful in planning next NOIRS, tentatively scheduled for 2018. NOIRS 2015 objectives for integration across disciplines and partnership with industry and safety professionals were partially met. In planning NOIRS 2018, more attention should be paid to attracting and engaging a broader spectrum of attendees.